Managing technology-based service innovations in emerging wellness business ecosystems - Annanperä, Elina; Oulun yliopisto. Tieto- ja sähkötekniikan tiedekunta (Acta Universitatis Ouluensis, ISSN 0355-3191, 2017)
As services are increasingly becoming the main focus in the traditional information communication technology industry, companies are seeking leverage from new types of collaborations, such as business ecosystems that cross industry boundaries. The health and wellness business is one service domain in which advances in technology have created the need for services that integrate technology in novel ways. To advance new service businesses, national research programmes offer funding for organisations to collaborate for developing innovative services. Forming new networks and collaboration between organisations is essential in the new business environment.Emerging business ecosystems formed in the research programme context are expanding the concept of business ecosystems. When organisations work together for the first time, challenges arise from bringing together different expectations and working styles. Additional challenges arise through issues regarding suitable integrations or in the creation of completely new services.The need to understand the practical phenomenon of emerging business ecosystems and the service innovation in these ecosystems formed the starting point of this research. The research was conducted in two separate Finnish research programmes in which the researcher actively participated. This led to the adoption of an action research strategy, comprising several activities focusing on the actor dynamics and roles as well as resolving issues arising from the ecosystem formation. In addition, the service innovation-focused research activities were based on the capabilities and domain expertise of the ecosystem companies.This research produced an understanding of the formation of wellness business ecosystems, identified the main phases of the formation and some challenges. This research found out that successful emerging business ecosystems require strong leadership early in the formation to maintain the stability and vision of the ecosystem, and each organisation should find its role within the ecosystem. The creation of viable services also requires openness between organisations. This research provides practical knowledge of the organisational actions, managerial insights and solutions to issues that are identified when organisations come together to form new ecosystems in a research programme context.
Keywords: Action research; aktionsforskning; digitalisaatio; företag; forskningsprojekt; hyvinvointiala; innovaatiot; innovationer; johtaminen; kehittämisprojektit; liiketoiminta; organisaatiot; organisoituminen; palveluliiketoiminta; palvelumuotoilu; roolit; teknologiayritykset; tietotekniikkayritykset; tjänstedesign; toimintatutkimus; tutkimusprojektit; verkostoituminen; verkostot; yhteistyö; yritykset; emerging business ecosystem; palveluinnovaatiot; research programmes; service design; service innovation; tutkimushankkeet; välfärssektorn